Inheritance of Egg Quality Traits in the Japanese Quail - Daikwo , S.I.; Dim, N.I.; Momoh, O.M. (International Journal of Poultry Science, 2013)
A total of 471 eggs were collected from 205 female Japanese quails at 20 weeks of age in 3 consecutive days. The mixed model least-squares and maximum likelihood computer programme of Harvey (1990) was applied to estimate heritability, genetic and phenotypic correlations of egg quality traits. The heritabilities of egg weight, egg length, egg width, egg shape index, shell thickness, albumen width, albumen height, Haugh unit, yolk width and yolk height were 0.37±0.09, 0.15±0.03, 0.40±0.17, 0.46±0.03, 0.52±0.03, 0.23±0.02, 0.27±0.14, 0.30±0.08, 0.11±0.03 and 0.11±0.02, respectively. The genetic correlations among egg quality traits ranged from -0.13 to 0.97. The phenotypic correlation between egg weight and albumen width, albumen height, yolk width and yolk height were positive and significant (P